Strategic Human Resource Practices in Building Professional Culture and Work Ethics for Sustainability - Khofifah Salsabila Dofitra; Lenny Christina Nawangsari (Journal of Sustainable Economic and Business, 2026)
The rapid growth of digital organizations requires the strengthening of professional culture and work ethics to ensure long-term business sustainability. However, the implementation of Strategic Human Resource Practices (SHRPs) in supporting this transformation remains inconsistent, particularly in rapidly expanding digital firms. Objectives: This study aims to explore the form and implementation of Strategic Human Resource Practices in building professional culture and work ethics, as well as to identify internal and external factors influencing their effectiveness in achieving business sustainability. Methodology: This research adopts a qualitative case study approach at PT Yuxi Jayatama Indonesia. Data were collected through in-depth interviews, organizational observations, and document analysis. Thematic analysis supported by NVivo was employed to identify patterns related to HR strategic alignment, leadership reinforcement, policy consistency, and cultural institutionalization. Finding: The findings indicate that SHRPs contribute significantly to shaping professional culture through structured HR systems, leadership commitment, and ethical reinforcement mechanisms. However, rapid organizational expansion, generational workforce characteristics, and inconsistent supervision create implementation gaps that moderate HR effectiveness. Conclusion: This study proposes a Strategic Human Resource Transformation Model that positions SHRPs as the foundational driver of cultural institutionalization and ethical reinforcement, demonstrating that sustainable business development in digital organizations depends on consistent strategic alignment rather than formal policy existence alone.